Poly[[aqua(μ5-1H-benzimidazole-5,6-dicarboxylato)(μ4-1H-benzimidazole-5,6-dicarboxylato)dibarium] 4.5-hydrate] - Zhang, Heng-Qiang; Zheng, Xiu-Jun; Zhao, Chun-Xiang; Ng, Seik Weng (International Union of Crystallography, 2011)
The polymeric title compound, {[Ba2(C9H 4N2O4)2(H2O)]·4. 5H2O} n, adopts a layer structure parallel to (001) in which adjacent BaII atoms are connected by two benzimidazole-5,6-dicarboxyl-ate dianions, one functioning in a 4-bridging mode and the other in μ5-bridging mode. The Ba atom having water in its coordination environment as well as the Ba atom without water exist in a nine-coordinate polyhedron of O atoms; the geometry is difficult to derive. Lattice water mol-ecules occupy the space between layers and inter-act with the layers through O - H⋯O, O - H⋯N and N - H⋯O hydrogen bonds. ne of the five lattice water molecules is equally disordered around an inversion centre and shows half-occupancy.